A legislação urbanística e os edificios residênciais privados modernos no centro da cidade de São Paulo entre 1927 e 1957 - Cipolla, Larissa Cataldi (2011)
The research examines the role of urban laws transformation in defining private housing developments, vertical and modern, through 1927 to 1957, in São Paulo city centre. The study is conducted based on three parameters of conceptualization and analysis, as follows: 1. Study of the development of modern and private housing architecture and town planning legislation in São Paulo city centre in the period of 1927 to 1957; 2. Volume assessment of 14 buildings selected for the reference period, taking into consideration: the legal limits for the area of construction, setbacks, jigs, the urban design, architectural typology, as well as the urban implantation. 3. Constraint interpretation of the relations between the urban and civic law changes and the project development of 14 buildings selected for the reference period, evaluating its implementation urban and urbanity